Maximum economic efficiency levels of cattle manure on growing cowpeas - Bezerra Neto, Francisco; Holanda, José Simplício de; Torres Filho, José; Torres, Jorge Ferreira (Pesquisa Agropecuaria Brasileira, 2014)
Experiments were carried out to define the maximum economic efficiency level on the yield of cowpeas (Vigna unguiculata (L.) Walp) and to observe the residual effect in the colonization project area of the Serra do Mel, RN, Brazil. Two experiments were established during the agricultural years of 1981 and 1982, in a soil of the Red-Yellow Alic Latosol type, where manure was applied the first year and the residual effect was assessed the second year. The experimental design was randomized complete blocks with four replications of eight treatments. The treatments were based on the manure levels which ranged from zero to 42 t/ha (dry basis), in intervals of 6 t/ha. In relation to the price ratio for 1981, the maximum economic efficiency level was 14 t/ha of manure with a yield of 337kg of grain/ha. In 1982 this level was 16 t/ha manure with a yield of 1539 kg of grain/ha. Among the yield components studied, only the number of pods per area reacted to different levels of cattle manure. One year after the application of manure, the levels of phosphorus and potassium in the soil were 15 ppm and 65 ppm, corresponding to five and two times more than the initial levels, respectively.